PENGGUNAAN WAKTU DAN SUHU YANG IDEAL PADA PROSES PENGERINGAN KADAR KARET KERING LATEKS - Andi Wijaya; Arief Rachmawan (Institut Teknologi Sawit Indonesia (ITSI), 2019)
Measurement of dryrubbercontent of latex (DRC) is very important factor in the trade transactions of rubber. Determination of temperature and drying time of latex’s DRC need to be studied in order to avo id the excessive difference between farmers and factories so that it can cause loss effect on sale andpurchase of latex transaction. This study aimed to determine the temperature and time factor of the DRC during the drying process and its interaction. The study used a complete random ized design (RAL) with twofactors, i.e. temperature (80oC, 90oC, 100oC, 110oC, 120oC) and time (2, 4, 6 hours) with 3 replications and as control was 100oC for 2 hours. The results showed that the interaction between temperature and time was apparent (p <0,010). The using of temperature variations of 90oC (4 and 6 hours), 110oC (2, 4, and 6 hours) and 120oC (2, 4, and 6 hours) is possible to replace standard temperature and time (100oC for 2 hours ), because it have no significant differences in the value of latex’s DRC.To prevent the latex sample browning and stickiness due to oxidation of high temperature, it can use temperature of 90oC-100oC and drying timeof 4-6 hours.